Photoshop 6.0 A to Z : - Bargh, Peter (Focal Press, 2001)
This quick, easy reference text is a must-have purchase for every Photoshop user. It is one of a kind – giving an easily accessible visual guide to all those vital Photoshop terms. Keep it next to your computer screen. It is a constant reference that will save you hours of frustration when the meaning of that term is on the tip of your tongue.